Sekolah Lapang Petani sebagai Community of Practice Pengembangan Inovasi Kelompok di Era Digital - Siti Amanah; Annisa Utami Seminar (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2022)
Farmer Field School (FFS) is a learning exchange method used by the farmers to find solution. In this digital era, farmers also exchange knowledge and information through digital platform. The research objective is to investigate the practices of FFS by farmers/female farmers in the form of Community of Practice nowadays. The research was conducted in Situgede Village, Bogor that has a typical of rural-urban community. Data on FFS, business groups and agricultural innovations were collected through in-depth interviews, observations and focus group discussions. The data and information were processed using NVivo software. The results show that the farmers practice FFS to solve on-farm issues, learning methods, cooperation and achieve the group’s objectives. The community groups used social media to communicate in addition to in person’s meetings. Situgede ecotourism development opens job opportunity and new business. The Dalima Female Farmer Group has produced organic red and black rice that sold through direct selling and via an e-commerce up to the end of 2021. One group run by youths produces herbal drink products. All groups have obstacles of water and land availability for agriculture, member participation, and innovation. The groups learn from other villages to solve the issues. In conclusion, FFS as a CoP is practiced based on the current issues faced in the fields.